PERLINDUNGAN HUKUM TERHADAP PENCIPTA SOFTWARE GAME DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Robby Akhmad Surya Dilaga (Jurnal IUS Kajian Hukum dan Keadilan, 2016)
The higher the age and quality enhancement technology, the higher the level of knowledge of technology, with a number of associations hackers and expert coding for trying to duplicate a video game that has been produced by the creators in the form of software, causing widespread also occur piracy of motive to get benefit financially, causing losses were not many, especially among the creators of video game software. Undue Act Law No.28 of 2014 on Copyright enforcement has also been applied effective from 16 October 2014 the pirates are able to make digital products a deterrent, but in fact a violation of intellectual property rights still occur even tend toward an increasingly alarming. One of the forms that offense is piracy Software game.Keyword : Protection, Copyright, Software Game